na citooo !!!!!
uporządkuj jednomiany :
3 (-x) (-a)
2cd * (-9)*d

uprość wyrażenie algebraiczne
4,5a + a -0,4a +0,4

zapisz w jak najprostszej postaci
9- (x + y ) - (2x+2y)
-(x-3y) - (4 -3x+ y )

wykonaj działania
-3(y-2) +4 (y+2)
5(x-y-1 ) -4 (x + 2)
2(3a+b) -2 (a-b)


Odpowiedź :

Odpowiedź:

3 (-x) (-a) = 3ax

2cd * (-9)*d = 2cd * (-9d) = -18cd²

4,5a + a - 0,4a + 0,4 = 5,1a + 0,4

9 - (x + y ) - (2x + 2y) = 9 - x - y - 2x - 2y = -3x - 3y + 9 = -3 (x + y - 3)

- (x - 3y) - (4 - 3x + y ) = -x + 3y - 4 + 3x - y = 2x + 2y - 4 = 2 (x + y - 2)

- 3 (y - 2) + 4 (y + 2) = -3y + 6 + 4y + 8 = y + 14

5 (x - y - 1 ) - 4 (x + 2) = 5x - 5y - 5 - 4x - 8 = x - 5 y - 13

2 (3a + b) - 2 (a - b) = 6a + 2b - 2a + 2b = 4a + 4b = 4 (a + b)